Dietary selective effects manifest in the human gut microbiota from species composition to strain genetic makeup - Kun D. Huang; Mattea Müller; Pavaret Sivapornnukul; Agata Anna Bielecka; Lena Amend; Caroline Tawk; Till-Robin Lesker; Andreas Hahn; Till Strowig (Cell Reports)
Summary: Diet significantly influences the human gut microbiota, a key player in health. We analyzed shotgun metagenomic sequencing data from healthy individuals with long-term dietary patterns—vegan, flexitarian, or omnivore—and included detailed dietary surveys and blood biomarkers. Dietary patterns notably affected the bacterial community composition by altering the relative abundances of certain species but had a minimal impact on microbial functional repertoires. However, diet influenced microbial functionality at the strain level, with diet type linked to strain genetic variations. We also found molecular signatures of selective pressure in species enriched by specific diets. Notably, species enriched in omnivores exhibited stronger positive selection, such as multiple iron-regulating genes in the meat-favoring bacterium Odoribacter splanchnicus, an effect that was also validated in independent cohorts. Our findings offer insights into how diet shapes species and genetic diversity in the human gut microbiota.